Penerapan Target Costing Sebagai Penentuan Harga Pokok Produksi Pada UMKM Kue Dongkal Ade - Armansyah, Alfaraby; Abdul Matin, Apin; Daffa Araehan, Mohammad; Ramadhan, Sandi (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
The Determination of Cost of Production can be interpreted as a step in the cost control process as well as in setting the selling price of a product. This study aims to analyze the calculation of the cost of production using the full costing method at Kue Dongkal Ade. This research uses a qualitative approach by conducting interviews as primary data and field observations as secondary data. The study demonstrates that the application of the full costing method is useful in providing more accurate information about production costs compared to the simple calculations made by the business owner. From the interviews conducted, it was found that the daily production cost is IDR 210,000, with 40 portions sold at a selling price of IDR 10,000 per portion, resulting in a profit of IDR 400,000 and a margin of 20%. The study concludes that the implementation of Target costing in determining the cost of production is highly efficient in helping business owners manage their operational activities.